Identifying and Designing Evidence-Informed Practice, in Practice: The Case for Pragmatic Evidence Synthesis Matrices (PESM) - Simon Knight (International Journal of Qualitative Methods)
Across sectors, including education, there are a confluence of pressures towards integration of research and evidence into practice. These include a focus on evidence quality in practice and policy, inclusion of research and evidence evaluation in professional training, and development of implementation standards and translational resources to support evidence mobilisation. However, while current approaches to evidence synthesis support many purposes, there is a gap in approaches to identify and design for evidence-informed practice ‘from within’ those practices. That is, current approaches may not adequately reflect the ways that practices: emerge and may be seen as ‘in need of evidence’; make use of proto-theories; and give rise to a need for clear alignment (or relevance) with evidence, and designed features of intervention contexts. This narrative review draws on an instrumental case to describe a novel method for Pragmatic Evidence Synthesis Matrices (PESM). PESM emerged from a body of work, particularly in educational technology (edtech), with one instrumental case briefly described to motivate its development. PESM: draws on extant evidence synthesis approaches, particularly best fit realist synthesis; integrates design artefacts including theory of change or logic model approaches and persuasive design; and is stakeholder oriented through use of narrative scenario-based methods. Through use of approaches such as PESM, evidence synthesis and systematised approaches to their development and use may be more readily developed across domains.